Mycosis Fungoides: The Great Masquerader – A Trilogy of Case Reports - Roy, Shipla; Ghosh, Kaustav; Mandal, Prakas Kumar; Das, Suchibrata (Asian Pacific Journal of Cancer Care, 2024)
Mycosis fungoides, also known as granuloma fungoides or Alibert-Bazin syndrome, is the most common form of primary cutaneous T-cell lymphoma. In the early stages of the disease, skin lesions can mimic a variety of other primary cutaneous disorders, including psoriasis, eczema, and tinea infections. Therefore, early suspicion, prompt diagnosis through histopathological and immunohistochemical analysis, and regular follow-up are crucial. This report presented a trilogy of cases demonstrating the varied skin lesions associated with mycosis fungoides.